Methodological Considerations for Survey-Based Research During Emergencies and Public Health Crises: Improving the Quality of Evidence and Communication - Kennedy, Eric B; Jensen, Eric A; Jensen, Aaron M (Frontiers in Communication, 2022)
COVID-19 has resulted in a massive amount of global research on the social and human dimensions of the disease. Between academic researchers, governments, and polling firms, thousands of survey projects have been launched globally, tracking aspects like public opinion, social impacts, and social/communicative drivers of disease transmission and mitigation. This deluge of research has created numerous potential risks and problems, including methodological concerns, duplication of efforts, and inappropriate selection and application of social science research techniques. Such concerns are more acute when projects are launched under the auspices of quick response, time-pressured conditions – and are magnified when such research is often intended for rapid public and policy-maker consumption, given the massive public importance of the topic. In this article, we provide a summary of key features of ‘rapid response’ survey research in science communication to COVID-19 and other emergencies, including suitability considerations that must be assessed before launching projects. We outline a series of best practices drawn from public opinion and evaluation research in the fields of public health, emergency management, and science communication research. We provide specific guidance about key methodological choices researchers must make, including sampling strategies, validation of measures, harmonization of instruments, and conceptualization/operationalization of research frameworks. Finally, we provide a summary of emerging networks, remaining gaps, and best practices for international coordination of survey-based research on human and social dimensions of COVID-19 and its long-term mitigation. This article is designed to contribute to improving the quality of research, evidence, and practices within ‘evidence-based science communication.’